The digital twin to represent the heat exchanger as the automation object through the parametric identification - Maksym, R.; Romashov, Yu. (Вид-во Іванченка І. С., 2024)
This research is about the development of the digital twin envisaged to represent the heat exchanger as the automation object. The digital twin is developed on the basis of the simplified assumptions, that the heat transfer between the heater and coolant mediums inside the heat exchanger is through the equivalent plane wall. The relations between the processes in the heat exchanger and the mathematical model representing this heat exchanger as the automation object are discussed.
Keywords: heat exchanger; digital twin; automation object; heat conduction